بلوچستان کے قبائل میں موجود توہمات شرعی نقطہ نظر ایک تحقیقی جائزہ: An exploratory review of superstation in tribal areas of Baluchistan from a shariah point of view - Amir Zaman Kakar; Muhammad Bilal; Dr. Hafiz Muhammad Khalid Shafi (Al Manhal Research Journal, 2023)
Allah is capable of everything, everything that happened in the universe, everything that is happening and everything that will happen all this is by his will. He alone causes harm and benefit, the time of death is fixed ,only he has the knowledge of the unseen, Allah created all things for the benefit of man nothing is sinister which is clearly supported in the hadith, Islam rejects superstitions and understand only Allah the real effective and all other creatures are under the command of Allah .there is no reality of bad omen in Islam ,however ,it is correct to consider good luck anything ,time and person as good about oneself , but doer is still Allah .superstition often reflect weak beliefs. Superstition are based on profit and loss however Allah is the only one who gives benefit and loss, some superstition predict good and bad time in the future, however the unseen is only Allah ,superstition are against Islamic beliefs .there are various superstition among the tribes of Baluchistan , the order of which will be explained individually but often superstition the tribes of Baluchistan are based on fabrication and lies which has nothing to do with Islam and reality.